2011
DOI: 10.1126/science.1203919
|View full text |Cite
|
Sign up to set email alerts
|

Role for piRNAs and Noncoding RNA in de Novo DNA Methylation of the Imprinted Mouse Rasgrf1 Locus

Abstract: Genomic imprinting causes parental origin–specific monoallelic gene expression through differential DNA methylation established in the parental germ line. However, the mechanisms underlying how specific sequences are selectively methylated are not fully understood. We have found that the components of the PIWI-interacting RNA (piRNA) pathway are required for de novo methylation of the differentially methylated region (DMR) of the imprinted mouse Rasgrf1 locus, but not other paternally imprinted loci. A retrotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
286
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 349 publications
(293 citation statements)
references
References 31 publications
3
286
1
3
Order By: Relevance
“…The imprinted Rasgrf1 locus is methylated on the paternal allele at a differentially methylated region (DMR) located 30 kb upstream of the promoter, and it is expressed only from the paternal allele (36). Interestingly, a recent study showed that Piwi-interacting RNAs (piRNAs), a subset of noncoding small RNAs, play a pivotal role in the establishment of methylation at the Rasgrf1 DMR (37). In contrast, we found the promoter CpG island of RASGRF1 to be hypermethylated in gastric cancer, and that this methylation is unlikely to be associated with gene imprinting.…”
Section: Discussionmentioning
confidence: 99%
“…The imprinted Rasgrf1 locus is methylated on the paternal allele at a differentially methylated region (DMR) located 30 kb upstream of the promoter, and it is expressed only from the paternal allele (36). Interestingly, a recent study showed that Piwi-interacting RNAs (piRNAs), a subset of noncoding small RNAs, play a pivotal role in the establishment of methylation at the Rasgrf1 DMR (37). In contrast, we found the promoter CpG island of RASGRF1 to be hypermethylated in gastric cancer, and that this methylation is unlikely to be associated with gene imprinting.…”
Section: Discussionmentioning
confidence: 99%
“…These prenatal piRNAs are involved not only in PTGS but also in TGS through de novo DNA methylation, because retrotransposons and at least one imprint control region are hypomethylated in Piwil2, Piwil4, and Pld6 (also known as mitoPLD) knockout prospermatogonia (Aravin et al 2007b;Carmell et al 2007;Kuramochi-Miyagawa et al 2008;Watanabe et al 2011). Thus, in the future, it might become possible to introduce epigenetic marks such as DNA methylation to specific genomic regions in germ cells, which could then be inherited by the progeny.…”
Section: Discussionmentioning
confidence: 99%
“…On first principles, and because of this plausibility argument, we suggest that it seems most likely that genomic imprinting exists and is maintained in mammalian genomes for several different reasons, and that the imprinting status of different genes might have quite different mechanisms of origin. It is clear, for instance, that the differentially methylated domain of Rasgrf1 was introduced by a transposable element, and its imprinting may be associated with co-option of the mechanism to silence the element (Watanabe et al, 2011). Contrasts of imprinting status of genes across different mammalian species also show acquisition of novel imprinted genes brought about by a genome rearrangement, bringing a formerly non-imprinted gene into the proximity of an imprinted gene cluster where it acquires allele-specific methylation and imprinting.…”
Section: Distinguishing Chromosomal Homologuesmentioning
confidence: 99%